The impact of knowledge management processes in pair programming practice - Ahmad, Mazida; Abdul Mutalib, Ariffin; Omar, Mazni; Yasin, Azman; Romli, Rohaida (Mirlabs, USA, 2015)
One of Extreme Programming practices is Pair Programming (PP) (the pair consists of a driver and a navigator), which is used for promoting knowledge sharing among students.This practice encourages students to think creatively on programming solutions, and simplify learning, especially for difficult courses such as Java. By applying PP, students are enforced to improve their social skills while communicating in the pair.Among the numerous benefits of PP, statistics show that knowledge sharing, communication, and transfer between the driver and the navigator can improve the code quality.Therefore, this study aims at proposing a conceptual model of a PP knowledge-based sharing for improving programming skills.In order to achieve the stated aim, PP-based laboratory assignments were conducted and the outcomes were compared to evaluate the impact of PP on code quality produced by participating students with and without adopting the conceptual model. The conceptual model has been validated by analyzing the collected data from the participants of PP-based laboratory assignment using Partial Least Square form of Structural Equation Modeling (PLS-SEM).In the end, this study found that socialization, combination, and internalization are the determinant factors for achieving better code quality in PP environment. The findings of this study would be benefiting the academic environment especially the Agile programmers in the PP domain.